Commonalities between ENT Specialists and Oral Medicine Experts: Old HPV Diseases and New Oral HPV-Cancer along the Borders - Giuseppina Campisi; Rodolfo Mauceri; Pietro Tozzo; Vera Panzarella (Oral, 2021)
A human papillomavirus (HPV) infection is globally one of the most common causes of sexually transmitted infections of the mucous membranes (genital, anal and oral). Over the last decade, an increasing number of young patients have been infected due to the changes in sexual habits in the general population. The majority of the lesions are benign; however, substantial scientific evidence has suggested a role for the HPV family in the carcinogenesis of squamous cell carcinoma (SCC). It is proposed that dentists, in addition to ENT specialists, should apply standardized management protocols in order to construct a well-defined pathway in terms of diagnosis, which is based on a PCR diagnostic technique and the management of those lesions.